Characteristics of implementah tion of credit transfer and accumulation system at technical universities of Kazakhstan - A. . Gazaliev; V. . Egorov; I. . Breido (Высшее образование в России)
Having joint to the Bologna convention in 2010, Kazakhstan has clearly emphasized furthervector of its movement – tendency to integration together with allHEuropean educational space.In Kazakhstan national credit system of higher education including the assessment of labor credits of each studying discipline and educational program based on AngloHSaxon credit model of education is created.Students of Kazakhstan study not only at universities of Europe, which implemented theEuropean credit system, but also at universities of America, Europe, Asia and Australia focused on other credit systems.According to the State Program of Education Development of the Republic of Kazakhstan for 2011 – 2020 the further reforms, which reduce the impact of centralized regulation and supervision and focus on the development of autonomy and academic freedom of universities,are planned.A gradual transfer from the technologies of studying abroad by the scheme: a student of Kazakhstan – the state – a foreign university, which exists nowadays, to the system of academic mobility: a university of Kazakhstan – a student – a foreign university with the financial support from the state is proposed.